Effectiveness of Inactive Archives Management in the Cooperative, Small and Medium Enterprises and Trade Service of Surabaya City - Cindy Afriliyanti Santoso; Rizky Nurhidayat Perdana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Managing inactive archives is a crucial element in government agency administration because it plays a role in maintaining document order, facilitating information access, and complying with applicable regulations. The Surabaya City Cooperatives, Small, Medium Enterprises, and Trade Office is responsible for managing inactive archives so that they can be used as reference sources, decision-making materials, and documentation of agency activities. This study aims to assess the effectiveness of inactive archives management, including archiving procedures, storage mechanisms, and the use of digital archives. The method used is qualitative with a descriptive approach, including observation, interviews with relevant staff, and document analysis as data sources. The research findings indicate that inactive archives management at this agency is running quite well, particularly in terms of recording, organizing, and digitizing archives. However, several obstacles remain, such as limited facilities and a lack of staff understanding of archiving procedures. In conclusion, the effectiveness of inactive archives management can be improved through staff training, providing adequate archival facilities, and implementing a consistent digital system. These improvements are expected to support smooth administration, facilitate information access, and optimize the function of inactive archives within the agency.